Registros na educação infantil : olhares sobre as infâncias e práticas pedagógicas potencialmente significativas para documentar - Botton, Fabiane da Motta (2023)
This master’s dissertation deals with the study of the construction process of “narratives of everyday life”, one of the forms of pedagogical documentation, in order to understand its function in kindergarten's education and for the school community. For this purpose, driven by Malaguzzi (1999); Ostetto (2017); Rinaldi (2021); Kuhlmann Jr (2011; 2015); Oliveira-formosinho (2007); Oliveira-formosinho and Formosinho (2019); Mello, Barbosa and Faria (2020); Davoli (2020); Barbosa (2006); among others, the theoretical framework was built to support the fieldwork based on the study of “narratives of everyday life” used as Pedagogical Documentation in a Rede Marista de Porto Alegre - RS’s school and in the analysis of questionnaire answers of 05 kindergarten teachers working in this school. The kindergarten school is an environment for the child's development and learning that takes place beyond a supposed curriculum of early childhood education, since everything that happens in the school routine is significant. Thus, through this study, it was concluded that there is an urgent need to rethink the pedagogical documentation to make it organic in the sense of recording the path, and not isolated practices, making it linear instead of punctual. Therefore, this master’s dissertation defends the premise that pedagogical work in kindergarten education through narratives requires collective work, and it doesn’t end with a project or the school period. It has to be divided between teachers and families, since narratives show paths taken by children and require pedagogy through dialogue